Hypokalemia Induced Arrhythmia during Pregnancy in Rural Area - A Case Report - Dicky Ardian; Fajar Hamonangan Panjaitan; Fatima Zahra (JURNAL KESEHATAN REPRODUKSI, 2026)
Hyperemesis gravidarum is a severe form of nausea and vomiting during pregnancy that leads to persistent fluid and electrolyte imbalances, with hypokalemia being among the most clinically significant complications. Hypokalemia disrupts normal cardiac membrane excitability and can precipitate lethal arrhythmias, including ventricular tachycardia, ventricular fibrillation, and torsade de pointes — rhythms that carry a substantial risk of sudden cardiac death if not promptly identified and treated. These life-threatening arrhythmias arise from hypokalemia-induced hyperpolarization of the cardiomyocyte resting membrane potential, which paradoxically heightens ventricular automaticity and creates a vulnerable electrophysiological substrate susceptible to malignant dysrhythmias. A 33-year-old multiparous woman at 29 weeks of gestation presented to the emergency unit with a three-day history of generalized weakness, fatigue, persistent nausea, vomiting exceeding five episodes per day, diffuse muscle cramping, and abdominal discomfort. On examination, she was tachycardic with an irregular pulse of 100 beats per minute and tachypneic at 24 breaths per minute. The initial electrocardiogram demonstrated ventricular bigeminy, and brief self-terminating runs of non-sustained ventricular tachycardia were subsequently observed — findings that signaled an evolving arrhythmogenic state with potential for progression to fatal ventricular arrhythmia. Laboratory investigations confirmed severe hypokalemia with a serum potassium level of 1.7 mEq/L. Two-dimensional echocardiography revealed no structural cardiac abnormalities with a preserved left ventricular ejection fraction of 60%. The patient was managed with intravenous potassium chloride replacement, empirical magnesium sulfate supplementation, Bisoprolol, and Methyldopa in the Intensive Care Unit. Serial electrocardiograms documented progression from ventricular bigeminy to trigeminy before complete resolution following serum potassium normalization to 3.4 mEq/L. This case demonstrates that hypokalemia secondary to hyperemesis gravidarum can induce lethal ventricular arrhythmias, and that favorable outcomes are achievable through early recognition and systematic management.